Desenvolvimento de ração protéica para abelhas apis mellifera utilizando produtos regionais do nordeste brasileiro - Pereira, Fábia de Mello (2005)
The objective of this research was to develop a protein diet for honeybees Apis mellifera using regional products of NE Brazil that are of easy access and reduced costs for beekeepers. Experiments were carried out between March 2001 and January 2005 in the “Núcleo de Pesquisa com Abelhas” (NUPA) of the Embrapa Meio-Norte in Teresina (5°05’ S and 42°49’ W) and in Castelo do Piauí (5º20’ S and 41º34’ W), Piauí, Brazil. Products selected at the beginning of the research were cassava hay (Manihot esculenta), leucaena hay (Leucaena leococephala), mesquite pod meal (Prosopis juliflora), “bordão-de-velho” pod meal (Pithecellobium cf. saman), babassu bran (Orbygnia martiana) and succedaneums for calfskin from Purina®. The performance of honeybees that consumed these components was compared with those that consumed pollen obtained from COORPEPÓLEN, Cooperativa de Pólen do Brasil, located in Canavieiras, Bahia, Brazil. Pollen fed to bees was predominantly Palmae pollen. Initial components selected were tested about toxic effects for honeybees; contents of crude protein, total soluble sugars, free amino acids, and contents of glycin, alanine, valine,leucine, isoleucine, phenylalanine, tyrosine, serine, methionine, asparagines, glutamine, aspartic acid, glutamic acid, lysine, arginine, histidine, asparagines and -aminobutyric acid. Results showed that the high content of sugars in the flour of “bordão-de-velho” does not allow its use for feeding honeybees, considering that it was observed an early mortality in the honeybees feeding with this meal. The other substances studied did not show any toxic effect, but only the leucaena hay have the contents of essential amino acids demanded by the honeybees. These results permitted the formulation of four diets: (T01) - 260 g of cassava hay, 140 g of mesquite pod meal, 437,39 g of sugar syrup and 0,96 g of vanilla essence; (T02) - 68 g of cassava hay, 332 g of babassu bran, 643,90 g of sugar syrup and 1,32 g of vanilla essence; (T03) - 304 g of babassu bran, 96 g of succedaneums for calfskin, 507,73 g of sugar syrup and 1,08 g of vanilla essence and (T04) – 500 g of pollen and 254,79 of sugar syrup. The feeds were tested for consumption, colony development and digestibility. Results showed that the three diets formulation did not show the same consumption and brood maintenance that pollen. However, by the end of the experiment all colonies were in better conditions than in the beginning, with higher food area and colony weight. The higher digestibility observed in the tests of digestibility could be attribute to the high consumption of sugar syrup and water. Results give evidence that all diets were efficient in maintaining the colonies strong and can be used by the beekeepers to maintain colony strength over the leanest period of the year. However, when the diet was the single source of protein, it was necessary to search for other alternative.